The Effectiveness of Interactive Powerpoint in Improving Students’ Conceptual Understanding of Optics (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
The purpose of using interactive powerpoint media is improving students' understanding of concepts. In the research that has been conducted involving 62 students of 11th natural science grade even semester of the academic year 2021/2022 at MAS PP Daarun Nahdhah Tawalib Bangkinang, Kab. Kampar, Prov. Riau. The first purpose of research is to describe students' conceptual understanding through the use of interactive powerpoint media. Second, to determine the effectiveness of using interactive powerpoint learning media in improving students' conceptual understanding. The type of research used is a quasi-experimental design with a non-equivalent posttest only control group design with 2 groups of participants, namely the experimental group and the control group. Based on the results of the descriptive analysis, it was found that the understanding of the concept of the experimental group was in the good category with an average achievement capacity of 73.2%. while the result of inferential analysis is that there is a difference in understanding of the concept of the experimental group and the control group with (sig) 0.000 <0.05. it can be concluded that the use of interactive powerpoint media can improve students' conceptual understanding of optical instrument material 11th grade MAS PP Daarun Nahdhah Tawalib Bangkinang.